Immunotoxicity and uterine transcriptome analysis of the effect of zearalenone (ZEA) in sows during the embryo attachment period. (1st March 2022) - Gao, Dengying; Cao, Xinxin; Ren, Huihui; Wu, Lihang; Yan, Youxin; Hua, Renwu; Xing, Wenkai; Lei, Minggang; Liu, Jian
Graphical abstract: Highlights: Systemic immunotoxicity of ZEA in diet on sows during embryo attachment period. 371 differentially expressed genes (DEGs) were identified in the RNA-seq. Immue pathways and Endometrial receptivity related genes were significantly enriched in the DEGs. It is the first time to explore the "ZEA-immune-embryo implantation" regulation axis. Abstract: Zearalenone is a mycotoxin and a pollutant that is commonly found in crops. Once ingested, ZEA can cause disturbances in the immune system and produce immunotoxicity. However, there is little research on the effect of ZEA exposure on the relationship between immune regulation and embryo implantation in the uteri of sows. Embryo implantation relies upon the fact that the relationship between the maternal and fetal immune systems is balanced. This balance is provided by the joint regulation of immune organs, cytokines, and uterine immunity. In this study, we investigated 20 sows with an initial weight of 100.00 ± 5.00 kg and 200 days in age. The sows were fed with diets containing ZEA at concentrations of 0 mg/kg, 1 mg/kg, 2 mg/kg, and 10 mg/kg, respectively, from 8 to 14 days of gestation. We studied immunotoxicity and the uterine transcriptomics associated with the effect of ZEA in sows during embryo attachment. Following ZEA treatment, serum biochemical analysis and RT-qPCR were used to detect the concentration and mRNA expression levels of immunoglobulin IgA, IgG, and IgM, in the serum and spleen, respectively. The same analysis was carried out for a range of cytokines in the serum and spleen: IL-1, IL-2, IL-6, IL-10, and TNF. Uterine transcriptome analysis revealed 75, 215, and 81 genes that were differentially expressed in the 0 mg/kg vs 1 mg/kg treatment, 0 mg/kg vs 10 mg/kg treatment, and 1 mg/kg vs 10 mg/kg treatment, respectively. GO terms analysis showed that the up-regulated genes related to the immune system were highly expressed. KEGG pathway analysis further revealed the importance of several metabolic pathways, including drug metabolism-cytochrome P450, the cytokine-cytokine receptor interaction pathway, and calcium signaling pathways. The differentially expressed genes were confirmed by quantitative real-time PCR. These findings expand our understanding of the gene expression profiles and signaling pathways associated with the immune response to ZEA exposure in sows during the embryo implantation window. This study provides valuable information for clarifying the molecular mechanism of ZEA's immunotoxicity to early pregnant sows in the future.